2008
DOI: 10.1111/j.1442-9071.2007.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar blood flow and ophthalmic perfusion in maximum dynamic exercise

Abstract: Maximal physical exercise increases OPP and blood flow at the OA without affecting blood flow at the CRA and SPCA, implying that auto-regulative mechanisms are active in both retinal and choroidal circulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
(93 reference statements)
1
9
0
2
Order By: Relevance
“…The IOP reduction after 15 min of treadmill running at a speed of 6.5-8 km/h was 3.82 mmHg, with an additional decrease of 1.14 mmHg after 30 min (Hong et al 2014). Kozobolis et al (2008) reported an IOP reduction of 5.6 mmHg after 1 min on the treadmill, at an intensity reaching 85% of the heart rate, although the positive effect lasted no longer than 30 min. Cycling.…”
Section: Dynamic Exercise and Iopmentioning
confidence: 93%
See 2 more Smart Citations
“…The IOP reduction after 15 min of treadmill running at a speed of 6.5-8 km/h was 3.82 mmHg, with an additional decrease of 1.14 mmHg after 30 min (Hong et al 2014). Kozobolis et al (2008) reported an IOP reduction of 5.6 mmHg after 1 min on the treadmill, at an intensity reaching 85% of the heart rate, although the positive effect lasted no longer than 30 min. Cycling.…”
Section: Dynamic Exercise and Iopmentioning
confidence: 93%
“…An elevation in OPP and blood flow (measured by colour Doppler imaging) at the ophthalmic artery but not in the central retinal artery or short posterior ciliary arteries was demonstrated after 30 min of exercise on the treadmill by Kozobolis et al., suggesting that autoregulation was involved in both retinal and choroidal circulations (Kozobolis et al. ). Okuno's group found that the retinal OBF [measured by scanning laser Doppler flowmetry (LDF)] increased immediately after 6 min of Master's double two‐step test, but returned to the baseline at 30 min postexercise, while the choroid–retinal blood flow [measured by laser speckle flowgraphy (LSFG)] continued to increase for 60 min (Okuno et al.…”
Section: Physical Exercise and Ocular Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 Comparing IOP values for each RT and control time point in the right eye reduction during aerobic activities. (16,17) However, this evidence is not adequate to explain IOP reductions associated with RT because, as opposed to aerobic exercise, RT is an intermittent activity with lower cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Kozobolis et al . report the short‐term (1 and 30 min) effects of maximum dynamic physical exercise on retrobulbar blood flow and ocular perfusion pressure (OPP) in 30 young healthy males, using colour Doppler imaging 14 . This study found OPP and peak systolic velocity (PSV) in the ophthalmic artery to be significantly higher at the 1‐min interval, compared with the pretest scores ( P = 0.01, in both cases), normalizing to pre‐exercise levels on the 30‐min post‐treadmill test.…”
Section: Low Diastolic Perfusion Pressure Found In Epidemiological Stmentioning
confidence: 99%